COMMUNICATION ORGANIZATIONAL PATTERNS TO REGIONAL DISASTER MITIGATION AFTER THE COVID-19 PANDEMIC - Adhrianti, Lisa; Ayyash, Muhammad Yahya; Alfarabi, Alfarabi; Warsah, Idi; Firmansyah, Mas Agus (Master of Communication Science Program, Universitas Diponegoro, 2024)
The COVID-19 pandemic, classified as a social disaster, continues to present challenges even in the post-pandemic era, especially in regions where public awareness and belief in the existence of COVID-19 remain low. This study focuses on identifying and analyzing the communication patterns employed by the Regional Disaster Management Agency (RDMA) of North Bengkulu Regency, Bengkulu Province, in mitigating the impact of the pandemic. The research aims to determine the organizational communication patterns within RDMA post-COVID-19 pandemic. A qualitative descriptive method was applied to explore the types and effectiveness of communication patterns—vertical, horizontal, and diagonal—used within the organization. The findings reveal that RDMA adopts a